a ANALISIS ASPEK LINGKUNGAN DAN PERILAKU KELUARGA DENGAN KASUS DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN SIALANGMUNGGU WILAYAH KERJA PUSKESMAS SIDOMULYO KOTA PEKANBARU, RIAU.doc - Hastuti Marlina (UNIVERSITAS BHAMADA SLAWI, 2016)
Environment is one of the factors that cause an illness. An environment that does not meet health requirements will cause problems, especially the occurrence of environmental-based diseases. Based on the profile data of the Pekanbaru City Health Office, cases of dengue fever have increased, from 20 existing Puskesmas in Pekanbaru City, the highest increase in dengue fever cases was found in Sidomulyo Health Center with a mortality rate of 10% in dengue fever in 2016. This study aims to analyze environmental aspects related to dengue fever cases in Sialang Village awaiting the working area of ​​Sidomulyo Health Center. The type of research used is descriptive qualitative. With the number of respondents 9 people with dengue hemorrhagic fever cases and 2 community leaders. The results showed that people with cases of dengue hemorrhagic fever in Sialangmunggu Village still had unclean and positive environmental conditions for the existence of pleace breeding and resting pleace Aedes agypti mosquitoes, the community had a good level of education and knowledge of dengue fever, but attitudes and behavior what is encountered in the field is still not good for the existence of breeding pleace and resting pleace in the community home.